Association Between Steroid-Sparing Therapy and the Risk of Perianal Fistulizing Complications Among Young Patients With Crohn Disease - Adler, Jeremy (JAMA Netw Open, 2020)
IMPORTANCE: Perianal fistulizing complications (PFCs) develop in 15% to 30% of patients with Crohn disease (CD), are difficult to treat, worsen quality of life, increase cost of care, and commonly recur. Evidence-based strategies to prevent PFCs are lacking. OBJECTIVES: To investigate the effectiveness of medical therapy for reducing risk of PFCs among young people with CD and to test the hypothesis that steroid-sparing therapy (SST) use would be associated with reduced risk of PFC development. DESIGN, SETTING, AND PARTICIPANTS: In this comparative effectiveness analysis of commercial administrative claims from January 1, 2001, through June 30, 2016, patients who did or did not initiate SST were matched via propensity score to adjust for all available confounders. Using Optum’s Clinformatics Data Mart, a deidentified database of US commercial administrative claims, all patients aged 5 to 24 years with CD (January 1, 2001, through June 30, 2016) were identified. The index date was the CD diagnosis date. Patients with PFCs or SST use at or before CD diagnosis were excluded. The dates of analysis were October 2017 to February 2020. EXPOSURES: The primary exposure of interest was SST initiation, including immunomodulators and/or anti–tumor necrosis factor α (anti-TNFα) medications, initiated before either PFC development or the end of the study period. MAIN OUTCOMES AND MEASURES: The primary outcome was PFC development. Propensity score matching was used to balance baseline characteristics. Cox proportional hazards multivariable regression analyses were used to estimate hazard ratios (HRs) with 95% CIs for PFC development. RESULTS: Among 2214 young people with CD without PFCs identified, the mean (SD) age at CD diagnosis was 17.0 (4.5) years, and 1151 (52.0%) were male. Among the cohort, 1242 patients (56.1%) initiated SST before PFC development or the end of 24-month follow-up. After propensity score matching, 972 patients remained in each treatment group. Overall, 384 of 1944 (19.8%) developed PFCs within 2 years of the index date. The use of SST was associated with a 59% decreased risk of PFC development (hazard ratio [HR], 0.41; 95% CI, 0.33-0.52; P < .001) in 2 years compared with no SST use. Among those who developed PFCs, 55% fewer SST users underwent ostomy than SST nonusers. The use of immunomodulators alone, anti-TNFα alone, and combination therapy was associated with 52% (HR, 0.48; 95% CI, 0.37-0.62; P < .001), 47% (HR, 0.53; 95% CI, 0.36-0.78; P = .001), and 83% (HR, 0.17; 95% CI, 0.09-0.30; P < .001) reductions in the risk of 2-year PFC development, respectively, compared with no SST use. CONCLUSIONS AND RELEVANCE: In this study, PFC development was common among young patients with CD. The use of SST was lower than expected. Compared with no SST, patients who initiated SST were 59% less likely to develop PFCs and fewer underwent ostomy. These results indicate that PFCs may be preventable and emphasize the importance of considering SST for all patients with CD.